Highly boosting the supercapacitor performance by polydopamine-induced surface modification of carbon materials and use of hydroquinone as an electrolyte additive. (10th April 2020) - Zhang, Zhong Jie; Deng, Guo Liang; Huang, Xuan; Wang, Xin; Xue, Jun Min; Chen, Xiang Ying
Abstract: In this work, we use polydopamine (PDA) to modify the surface of carbon materials, and then adopt hydroquinone (HQ) as a redox additive to jointly improve the performance of supercapacitors. This non-covalent bond PDA coating produce functional groups such as amino and hydroxyl, which can interact with HQ in H2 SO4 system by hydrogen bonding. The carbon materials solely coated with PDA (without any HQ) deliver favorable capacitance of 218 F g −1 and energy density of 7.59 Wh kg −1 ; whereas the one not only coated with PDA but also using HQ as redox additive, higher capacitance of 557 F g −1 and energy density of 19.36 Wh kg −1 are achieved, realizing the energy density increases by 2.55 times. In addition, for carbon materials not covered with PDA, HQ kinetics is diffusion controlled; for carbon materials covered with PDA, HQ kinetics is surface controlled. Obviously, this work provides a synergistic approach to collectively boosting the performance of supercapacitors. Graphical abstract: Image 103729 Highlights: Coating PDA on the surface of carbon material will reduce porosity. The thin layer of PDA is combined with HQ through hydrogen bonding. PDA and HQ undergo redox reactions and generate pseudo-capacitance. Without PDA, HQ kinetics is diffusion controlled; with PDA, HQ kinetics is surface controlled. By adding HQ, the energy density increases by 2.55 times, also exhibiting excellent cycling stability.